2018
DOI: 10.1007/s10856-018-6178-6
|View full text |Cite
|
Sign up to set email alerts
|

An important step towards a prevascularized islet microencapsulation device: in vivo prevascularization by combination of mesenchymal stem cells on micropatterned membranes

Abstract: Extrahepatic transplantation of islets of Langerhans could aid in better survival of islets after transplantation. When islets are transfused into the liver 60-70% of them are lost immediately after transplantation. An important factor for a successful extrahepatic transplantation is a well-vascularized tissue surrounding the implant. There are many strategies known for enhancing vessel formation such as adding cells with endothelial potential, the combination with angiogenic factors and / or applying surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Dense vascularization in the implant vicinity is imperative for adequate islet oxygenation. Various strategies to increase angiogenesis including surface micropatterning [41], seeding with proangiogenic cell populations [42,43], and immobilization of growth factors have been recently reviewed [44] (Figure 2A). ViaCyte Inc. and W. L. Gore & Associates Inc. are conducting a Phase I/II trial to study the safety and tolerability of a proprietary expanded polytetrafluoroethylene (ePTFE) membrane functionalized for improved surface vascularization of the PEC-Encap device (NCT04678557).…”
Section: Glossarymentioning
confidence: 99%
“…Dense vascularization in the implant vicinity is imperative for adequate islet oxygenation. Various strategies to increase angiogenesis including surface micropatterning [41], seeding with proangiogenic cell populations [42,43], and immobilization of growth factors have been recently reviewed [44] (Figure 2A). ViaCyte Inc. and W. L. Gore & Associates Inc. are conducting a Phase I/II trial to study the safety and tolerability of a proprietary expanded polytetrafluoroethylene (ePTFE) membrane functionalized for improved surface vascularization of the PEC-Encap device (NCT04678557).…”
Section: Glossarymentioning
confidence: 99%
“…Here, we show that our device allows rapid vascularization. We applied the intermitted microstructured lid which can guide vascularization in vivo, as shown in an earlier study using MSCs [15]. To allow this degree of vascularization, we applied a distance between the lines of 100 µm, since it has been shown that cell alignment occurs in patterns between 20 and 130 µm [27].…”
Section: Discussionmentioning
confidence: 99%
“…This device can prevent islet aggregation and support functional islet survival in vitro [14]. Besides, when a micropatterned lid is applied, the device can induce alignment of mesenchymal stem cells (MSCs) in vitro and contribute to improved vascularization in vivo [15]. Moreover, recently, based on modeling studies we proposed an improved device with optimal spatial distribution of oxygen gradient and insulin secretion [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, developing a well‐vascularized graft is important for extrahepatic transplantation success. Different strategies have been proposed in the past to improve the vascularization around the islet graft via delivering of angiogenic growth factors, co‐culture of MSCs or endothelial cells, or application of micro‐patterned bioactive scaffolds . Nowadays, many research groups have been focusing on developing subcutaneous islet transplant modalities as this site is attractive namely due to the feasibility of housing larger transplant volumes facilitating the co‐transplantation of islets with cytoprotective cells, minimal invasiveness surgery, and accessible for real‐time graft monitoring …”
Section: Discussionmentioning
confidence: 99%